LITERATUR REVIEW : EFEK PENDAPATAN DAN SUBSTITUSI DITINJAU DARI EKONOMI ISLAM DAN KONVENSIONAL - Doni, Amsah Hendri; Al-Amin, Al-Amin; Alfiona, Fifa (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
The effect of income and substitution is a change in food consumption caused by an increase in purchasing power, with prices relatively constant. The purpose of this study is How the effect of income and substitution effects is seen from Islamic and conventional economics. This research method This research includes a type of library research; namely data and study materials that are included in use come from literary sources, both in the form of books, encyclopedias, journals, magazines, newspapers, papers and others. The results of this study are Things that cause changes in the substitution effect (SE) and income effect (IE), With the change in price, you will have two impacts that occur. Thus price changes will result in the quantity of goods requested will increase or decrease depending on the resultant of the two impacts. In Islamic economics the level of consumption of these goods is usually termed daruriyat, tahsiniyat, and hajiyat goods